2002
DOI: 10.1111/1467-629x.00073
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management surrounding CEO changes

Abstract: This paper investigates the extent of earnings management in the periods surrounding CEO changes by Australian firms. Evidence is presented of incoming CEOs undertaking earnings management to reduce income in the year of CEO change, with abnormal and extraordinary items being the primary vehicle through which this is achieved. This result is consistent with the notion of new CEOs engaging in an ‘earnings bath’, and is strongest for non–routine CEO changes, where the opportunities to manage earnings are greates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
142
0
21

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(174 citation statements)
references
References 16 publications
11
142
0
21
Order By: Relevance
“…As we are unable to identify executives who only very narrowly evaded replacement only, discretion exerted by the incumbent is once more hard to detect. Both reasons may explain why previous studies (e. g. Wells (2002), Davidson III et al (2007)) find only limited evidence of discretion exerted by the departing CEO during the turnover year.…”
Section: Hypothesesmentioning
confidence: 91%
See 1 more Smart Citation
“…As we are unable to identify executives who only very narrowly evaded replacement only, discretion exerted by the incumbent is once more hard to detect. Both reasons may explain why previous studies (e. g. Wells (2002), Davidson III et al (2007)) find only limited evidence of discretion exerted by the departing CEO during the turnover year.…”
Section: Hypothesesmentioning
confidence: 91%
“…The literature (e. g. Pourciau (1993), Wells (2002)) investigates differences in the way managerial discretion is exerted during so-called routine CEO changes on the one hand and non-routine ones on the other. Whereas a routine turnover is characterized by a relatively orderly CEO succession process, a bank may not have the opportunity to adequately structure a non-routine turnover.…”
Section: Hypothesesmentioning
confidence: 99%
“…Previous studies (Wilson & Wang, 2010;Conyon & Florou, 2004;Reitenga & Tearney, 2003;Godfrey, Mather, & Ramsay 2003;Wells, 2002;Brickley, Linck, & Coles, 1999;Pourciau, 1993;Dechow & Sloan, 1991) have indicated that CEO turnover is commonly related to earnings quality. Thus, we included a factor for CEO turnover in a reexamination of our third hypothesis, the results of which are listed in Table 9.…”
Section: Consider the Ceo Turnovermentioning
confidence: 98%
“…Earlier literature reported a positive association between the tenure of CEO and earnings management behaviors, as measured by discretionary accruals (Wells, 2002;Goodfrey, 2003) and assets write-offs (Strong & Meyer, 1987;Elliott & Show, 1988). More recently, researches have investigated the relation between CEO change and goodwill write-offs, in the transition period (Beatty & Weber, 2006;Zang, 2008;Lapointe-Antunes et al, 2008) and in the post-adoption period (Guler, 2006;Masters-Stout et al, 2008;Stumpell, 2012;Ramanna & Watts, 2012;Al Dabbous et al, 2015) and have proved that new managers tend to use the discretion afforded by the goodwill impairment process under IAS 36, in order to reduce earnings.…”
Section: Change In Senior Managementmentioning
confidence: 99%